Effects of eustress induced by low concentrations of salinity on broccoli (Brassica oleracea) and purslane (Portulaca oleracea) microgreens - Gretchen Plocek; Shivani Kathi; Catherine Simpson (Technology in Horticulture)
Most controlled environments utilize municipal water for crop irrigation. Many of these sources exceed the EPA guidelines of < 500 mg·L−1 total dissolved salts. Issues can arise when tap water with the above limit salt concentrations is used for irrigation. Eustress is defined as the use of slight stress (from stressors such as salinity, temperature, or light) to induce positive effects without distress. While eustress is commonly used on mature plants, the effects on early growth stages of plants, such as microgreens, are not well documented. As microgreens are typically more stress sensitive, the concentrations of salinity to induce eustress may be lower than for mature plants. To identify how eustress affects microgreens, salinity concentrations commonly found in tap water were used in these experiments. Brassica oleracae (moderately salt tolerant) and Portulaca oleracea (highly salt tolerant) microgreens were evaluated. Both species of microgreens were cultivated using salinity irrigation treatments ranging from 0 dS·m−1 to 1.5 dS·m−1. Plants were analyzed for microgreen yield (fresh weight and dry weight), percent moisture content (% MC), percent dry matter (% DM), vitamin C (T-AsA, AsA) and proline concentrations. The results indicate that yields of both variety remained unaffected by the salinity treatments. However, %MC and proline significantly increased under 1 and 1.5 dS·m−1 NaCl in broccoli. Vitamin C also decreased as salinity increased in broccoli microgreens. Purslane microgreen vitamin C and proline remained unaffected by salinity. In conclusion, while low salinity levels had no negative impacts on microgreen yields, there were varied impacts on the phytochemistry between each variety.